2008
DOI: 10.5195/jyd.2008.284
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-School Time Activity Participation, School Engagement and Positive Youth Development: Findings from the 4-H Study of Positive Youth Development

Abstract: Abstract:The relations in early adolescence among out-of-school-time activities and indicators of youth development were assessed through the use of 8th grade data from the longitudinal, 4-H Study of Positive Youth Development. Hierarchical multiple linear regressions indicated that "hanging out" with friends without set plans and excessive media use were associated with lower behavioral engagement with school, lower academic achievement, and higher rates of risk behaviors. Youth who ate dinner with their fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 20 publications
1
32
0
2
Order By: Relevance
“…O desempenho académico, entendido como rendimento e comportamento escolar, tem vindo a ser relacionado com o nível de envolvimento dos estudantes na escola (Finn, Pannozzo, & Voelkl, 1995), em grupos de diferentes idades (Finn & Rock, 1997;Ryan & Deci, 2000;Skinner, Wellborn, & Connell, 1990). Na generalidade, o envolvimento tem sido associado com o desempenho académico (Li, Bebiroglu, Phelps, Lerner, & Lerner, 2008;Marks, 2000), com a aprendizagem (Ainley, 1993;Miller, Greene, Montalvo, Ravindran, & Nichols, 1996), com os resultados escolares, com o desempenho em testes estandardizados (Caraway, Tucker, Reinke, & Hall, 2003;Finn & Rock, 1997) e com as taxas de escolaridade concluída, registando-se relações estatisticamente significativas e no sentido esperado entre diferentes dimensões do envolvimento e estas variáveis. Finn (1993) estudou a relação entre o envolvimento (participação) e o desempenho escolar, tendo encontrado uma forte associação entre os dois constructos, independentemente do género e do nível socioeconómico.…”
Section: Envolvimento E Desempenho Académicounclassified
“…O desempenho académico, entendido como rendimento e comportamento escolar, tem vindo a ser relacionado com o nível de envolvimento dos estudantes na escola (Finn, Pannozzo, & Voelkl, 1995), em grupos de diferentes idades (Finn & Rock, 1997;Ryan & Deci, 2000;Skinner, Wellborn, & Connell, 1990). Na generalidade, o envolvimento tem sido associado com o desempenho académico (Li, Bebiroglu, Phelps, Lerner, & Lerner, 2008;Marks, 2000), com a aprendizagem (Ainley, 1993;Miller, Greene, Montalvo, Ravindran, & Nichols, 1996), com os resultados escolares, com o desempenho em testes estandardizados (Caraway, Tucker, Reinke, & Hall, 2003;Finn & Rock, 1997) e com as taxas de escolaridade concluída, registando-se relações estatisticamente significativas e no sentido esperado entre diferentes dimensões do envolvimento e estas variáveis. Finn (1993) estudou a relação entre o envolvimento (participação) e o desempenho escolar, tendo encontrado uma forte associação entre os dois constructos, independentemente do género e do nível socioeconómico.…”
Section: Envolvimento E Desempenho Académicounclassified
“…improved self-esteem, motivation and selfefficacy, increased pro-social bonding, cognitive, social and emotional competence, increased personal and social skills, higher levels of youth civic engagement, higher levels of behavioral and emotional engagement with school, and improved academic performance and so on. 34,35 A bulk of the studies have focused on youth at risk and utilized content targeting education about the specific kinds of risk in question (substance use, sexual and reproductive health, youth from slums or poverty ridden areas, etc. ), though there are a few that have focused on general samples of youth.…”
Section: Pyd Based Youth Mental Health Promotionmentioning
confidence: 99%
“…One approach to help foster more positive and inclusive peer culture is youths' engagement in structured after-school programs that focus on youth development (e.g., 4-H, Boy Scouts and Girl Scouts, YMCA, Boys and Girls Club, etc.) and time spent involved in civic engagement (Li, Bebiroglu, Phelps, Lerner, & Lerner, 2008). Li and colleagues found that youths' increased time spent engaged in meaningful out-ofschool activities deterred them from engaging in adverse activities.…”
Section: Resultsmentioning
confidence: 99%